Type 2 Diabetes Mellitus, a Sequel of Untreated Childhood Onset Growth Hormone Deficiency Developing in a 17-Year-Old Patient - Rohan K. Henry; Ram K. Menon (Case Reports in Endocrinology)
In a seminal report, a 17-year-old boy with panhypopituitarism had fatty liver (FL) amelioration with growth hormone (GH). By extension, since hepatic insulin resistance (IR) is key to FL and type 2 diabetes mellitus (T2DM), GH then may ameliorate the IR of T2DM. We present a 17-year-old nonobese female with untreated childhood onset growth hormone deficiency (CO-GHD) who developed type 2 diabetes mellitus (T2DM) and steatohepatitis with bridging fibrosis. Based on height z-score of – 3.1 and a history of radiation therapy as treatment for a medulloblastoma at 7 years of age, GHD was quite likely. GH therapy was, however, not initiated at 15 years of age (when growth was concerning) based on full skeletal maturity. After she developed T2DM, GHD was confirmed and GH was initiated. With its initiation, though insulin dose decreased from 2.9 (~155 units) to 1.9 units/kg/day (~ 100 units), her T2DM was, however, not fully reversed. This illustrates the natural history of untreated CO-GHD and shows that though hepatic IR can be ameliorated by GH, full reversal of T2DM may be prevented with irreversible hepatic changes (fibrosis). Clinicians caring for pediatric patients and otherwise should remember that, even in patients beyond the cessation of linear growth, GH can have a crucial role in both glucose and lipid metabolism.